Effect of climate factors on survival and growth of planted trees in scots pine (pinus sylvestris l.) plantations (Mongolian Journal of Agricultural Sciences, 2019)
This study was conducted in planted forests located in the Tujyin Nars National Park territory of Selenge province, Mongolia. We aimed at studying the effect of climate factors on seedling survival and tree growth at the Scots pine plantations. A total of five 50 x 20 m (0.1 ha) sized square sample plots were established at the plantations, planted between 2003 and 2007. All field measurements and data collection were carried out annually in September and October between 2003 and 2017. Annual field measurements of seedlings included: tree health status, diameter at stem basis, total height and annual height increments. We used climate data taken from the closest meteorological station (8-15 km to the north-west), “Sukhbaatar” located in Sukhbaatar Soum of Selenge province. To calculate the statistical analysis of the survival rate and seedling growth, we used the one-way analysis of variance (ANOVA) method to determine statistically significant differences in means among variables between the sites. An F-test and Pearson's correlation coefficient were used to assess the relationships between climate variables and survival and tree growth. Our findings showed a significant difference (F=28.4, p